The Influence of the Problem Posing Learning Model on Students' Mathematical Problem Solving Abilities in One-Variable Linear Materials - Pamungkas, Magita Danang; Ali, Mohamad Bilal (Tematik : Jurnal Konten Pendidikan Matematika, 2024)
The primary objective of this study is to investigate the impact of the problem posing learning model on the mathematical problem solving abilities of seventh-grade students in the topic of one-variable linear equations. The study aims to determine the extent to which the problem posing learning model influences students' mathematical problem solving abilities at SMPN 2 Gading. Additionally, the study seeks to examine the students' learning activities during the implementation of the problem posing learning model in the context of one-variable linear equations, and to evaluate the effectiveness of implementing the problem posing learning model for seventh-grade students at SMPN 2 Gading. The sampling technique employed in this study is purposive sampling with a simple random sampling approach. The data collection involves essay questions comprising three items to assess students' mathematical problem solving abilities. These questions were pre-tested for validity, reliability, distinguishing power, and level of difficulty. The findings of the research indicate a significant influence of the problem posing learning model on the mathematical problem solving abilities of seventh-grade students at SMPN 2 Gading. The effect size value is reported to be 4.202, indicating a substantial impact. Moreover, the study observes a change in student activities during the learning process, with an increase in student engagement, particularly during the second meeting. The implementation of the problem posing learning model for seventh-grade students at SMPN 2 Gading is reported to have proceeded smoothly from the first to the last meeting.